Schubert : the songs - Schubert, Franz Peter 1797-1828 ([Lugar de publicación no identificado] : CD Sheet Music, 2000)
Sumario: Presenta 598 canciones, en el tono original, y también con alteraciones. Agrupándolas en ciclos; y con la posibilidad de apreciar su partitura.
Requisitos del sistema: Microsoft Windows 95, 98, NT 4.0, 2000; 10 MB RAM on Windows 95, 98 (16 MB recommended), 16 MB RAM on Windows NT (24 MB recommended), 10 MB of available hard-disk space Systems requirements for Macintosh': Apple Power Macintosh or compatible; Systerm 7.5 or later, 4.5 MB of available RAM (6.5 MB recommended), 8 MB of available hard-disk space. Data accessed by Adobe Acrobat' Reader 4 software included on the disk--Exclusive distributor, Theodore Presser Co.
Keywords: CANCIONES; MUSICA CLASICA; VOCES CON PIANO; COLECCIONES; PARTITURAS